Advantages of real-time transabdominal ultrasound guidance in combined interstitial/intracavitary cervical brachytherapy: a case-based review - Thibodeau, Ryan; A. Simone, Brittany; Tanny, Sean; Shin Hahn, Seung; D. Aridgides, Paul (Journal of Contemporary Brachytherapy, 2021)
Sub-optimal placement of both intracavitary devices and interstitial needles is a relatively common occurrence in cervical brachytherapy, which may reduce the accuracy of dose distribution and contribute to adverse toxicities. To mitigate complications, improve target dose coverage, and verify proper device placement, implants may be placed under real-time image guidance. Traditionally, transrectal ultrasound has been used for needle guidance. However, we have utilized transabdominal ultrasound (TA-US) in our brachytherapy center. The purpose of this pictorial essay was to provide a pictorial description of TA-US technique, present a retrospective review of our preliminary outcomes adopting TA-US into routine practice, and to discuss the advantages of real-time ultrasound image guidance for placement of intrauterine tandem and interstitial needles.